Utilization and Effectiveness of Free Newborn Care Service Package in Inpatient Care of Sick Newborns –A Time For its Revision to Ensure Sustainability: Evidences From a Tertiary Level Public Hospital in Nepal - Paudel, Prajwal; Subedi, Kalpana Upadhyaya; Karmacharya, Shailendra Bir; Shrestha, Sarita; Shrestha, Anil Kumar; Subedi, Pratikshya; Sah, Sunil Kumar; Mishra, Megha; Tamrakar, Asia; Khati, Nisha; et al. (Journal of Nepal Paediatric Society, 2021)
Introduction: Free Newborn Care (FNC) service has been implemented to address the financial barriers to access sick newborn care in Nepal. This study was designed to evaluate the effectiveness of FNC package in terms of its adequacy to support a facility financially and the factors to be considered for reimbursement schemes in the FNC guideline. Methods: This is a cross sectional retrospective study where 2907 newborns who received FNC service from 2019 Mar 15 to 2021 Jan 14 over 20 months were included. Descriptive statistics using frequency and percentages were used to describe the package received. Pearson’s Chi squared test was used to determine if the various factors receiving different newborn packages were statistically significant or not. Results: Amount reimbursed by FNC package for 20 months fell short by NRs 1355541. Majority of preterm (58%), LBW (52.3%) and MAS (55.3%) received package C. Babies who received package C with single morbidity was 576 (37.3%) with two to three morbidities was 380 (48.7%) and with more than three morbidities was 301 (70.2%). Those newborns who stayed for four to seven days, majority 654 (53.4%) received package B, whereas those who stayed for eight to 14 days, 15 - 21 days and > 21 days, the majority 490 (38.4%), 66 (5.2%), 32 (2.5%) received package C respectively. There was an association between receiving package C mortality among cases (P < 0.001). Conclusions: Inpatient quality newborn care can save lives of many vulnerable newborns. FNC service has provided opportune context in care of sick newborns with promising results. However, revising the reimbursing schemes by focusing on length of stay, mortality and disease severity can better strengthen sick newborn care.